Management methodology based on lean construction and pmbok; To improve productivity in construction projects. - Margot Millones Mateus (2020)
The article presents the results about processes related to project management, with the aim of proposing a methodology based on Lean Construction and the fundamentals of the PMBOK Guide; that allows to improve the productivity of construction projects. The methodology obtained from integrating the Last Planner Planning scenario, the planning process group, as well as the PMI scenario monitoring and control process group (Fundamentals of the PMBOK Guide); will optimize the factors that affect the planning and monitoring and control of construction projects by improving their productivity; reflected in the improvement of the quality, time and cost of the project. The optimization of the Sub-profile profiling process without material input generated great results (outputs) such as the reduction of the time (execution period) from 98 days to 68 days and the reduction of the cost of S/. 255,851.59 to S/. 230,061.70; these outputs are per unit of consumption (inputs) corresponding to the efficiently managed resources (labor, equipment and materials) and an effective quality control.